Vegetation runoff and sediment reduction benefits and influential factor in the Loess Plateau of China: A meta-analysis - Mengrou Jia; Cong Han; Jianzhi Niu; Miao Wang; Linus Zhang; Ronny Berndtsson (Ecological Indicators)
The Loess Plateau is one of the most severely affected regions in China by soil erosion, where vegetation restoration is the principal strategy for soil and water conservation. Runoff and sediment reduction benefits (RRB and SRB) are key indicators used to evaluate the effectiveness of vegetation measures. While numerous observational and experimental studies have explored the effects of different vegetation types and climatic factors on RRB and SRB, the spatial variability and environmental controls of these benefits in the Loess Plateau remain insufficiently understood. This meta-analysis synthesizes data from 74 published studies, compiling a total of 1,518 data points derived from three vegetation types: forest, shrubland, and grassland. It analyzes the spatial variability of RRB and SRB, along with their relationships with vegetation, climatic, and geographic factors. The results indicate that RRB and SRB are highest in shrubland and lowest in grassland, with SRB generally exceeding RRB across all vegetation types. Both RRB and SRB are influenced by various environmental factors, with mean annual precipitation and vegetation cover exerting the greatest impact. Identified thresholds indicate that especially RRB (or SRB) is maximized at a stand age of 15–20 years, on slopes of 25–30° (20–25° for SRB), or with vegetation cover of 65–70 % (55–60 % for SRB). Vegetation measures significantly enhance soil and water conservation in the Loess Plateau. However, vegetation restoration should account for regional environment and require species suited to local conditions. Additionally, maintaining plantations regularly throughout the vegetation lifecycle is essential to achieve long-term sustainable results.